2019
DOI: 10.1098/rsob.180265
|View full text |Cite
|
Sign up to set email alerts
|

Understanding intellectual disability and autism spectrum disorders from common mouse models: synapses to behaviour

Abstract: Normal brain development is highly dependent on the timely coordinated actions of genetic and environmental processes, and an aberration can lead to neurodevelopmental disorders (NDDs). Intellectual disability (ID) and autism spectrum disorders (ASDs) are a group of co-occurring NDDs that affect between 3% and 5% of the world population, thus presenting a great challenge to society. This problem calls for the need to understand the pathobiology of these disorders and to design new therapeutic strategies. One a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 409 publications
(571 reference statements)
0
40
0
1
Order By: Relevance
“…The altered E/I ratio in VPA animals observed at 3M suggested downregulation of excitatory synapses at this age; moreover, there might be abnormal regulatory mechanisms of excitatory synapses. Previous studies on ASD model rodents have reported that long-term depression (LTD) is affected 23 . To determine whether VPA exposure affected LTD of excitatory synapses, we recorded the field EPSPs in layer 3 evoked by layer 4-5 stimulation, and induced LTD by low frequency stimulation (LFS, 1 Hz, 15 min).…”
Section: Resultsmentioning
confidence: 99%
“…The altered E/I ratio in VPA animals observed at 3M suggested downregulation of excitatory synapses at this age; moreover, there might be abnormal regulatory mechanisms of excitatory synapses. Previous studies on ASD model rodents have reported that long-term depression (LTD) is affected 23 . To determine whether VPA exposure affected LTD of excitatory synapses, we recorded the field EPSPs in layer 3 evoked by layer 4-5 stimulation, and induced LTD by low frequency stimulation (LFS, 1 Hz, 15 min).…”
Section: Resultsmentioning
confidence: 99%
“…ASD, the most prevalent neurodevelopmental disorders, is used to define a clinically heterogeneous group of disorders, while it generally exhibits two core symptoms, impaired social communication and repetitive behaviors (Bhat, Acharya, Adeli, Bairy, & Adeli, 2014;Fakhoury, 2015). A large number of risk genes that are associated with ASD pathogenesis have been identified (Nakanishi, Anderson, & Takumi, 2019;Verma, Paul, Amrapali Vishwanath, Vaidya, & Clement, 2019). Studies on ASD-related genes have indicated an altered axonal growth, an imbalance in neural network excitation/inhibition, and an impaired synaptic plasticity in the corticostriatal pathway (Fuccillo, 2016;Golden, Buxbaum, & De Rubeis, 2018;Kuo & Liu, 2019;Shepherd, 2013).…”
Section: Corti Cos Triatal Dys Fun C Ti On and A S Dmentioning
confidence: 99%
“…For example, genes that encode physically interacting proteins, which are co-regulated or co-evolving, are more likely to work in a common process. In addition, studies on single gene mouse models of ID reveal that the effects of these mutations converge onto similar or related etiological pathways, highlighting common pathological nodes that can help in the understanding of new ID related genes [28] . The huge collection of mutant model organisms and the literature can be reviewed to study ID related phenotypes, keeping in mind the mode of inheritance demonstrated in humans when choosing the model to study.…”
Section: Functional Understanding Of Id-related Genetic Variantsmentioning
confidence: 99%